(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In this study, we examine During solar cycles 23 and 24, the Galactic cosmic-ray (GCR)oscillations were explored using data from NASA’s Advanced Composition ExplorerCosmic Ray IsotopeSpectrometer instrument and ground-based neutron monitors (NMs). The findings show that at the solarminimum in 2019-2020, the maximum GCR intensities of heavy nuclei (5 Z 28, 50500 MeV nuc1) at 1 auexceed previous records by about 25 and 6, respectively, and reach their highest values throughoutthe space age. Peak NM count rates, on the other hand, are lower than in late 2009. The difference in NMcount rates and GCR intensity is currently unaccounted for. Furthermore, we discover that the GCRmodulation environment P2425 of the solar minimum varies from previous solar minima in key ways acomparatively small amount of sunspots There is very little tilt in the heliospheric current sheet, rarecoronal mass ejections, a weak interplanetary magnetic field, and turbulence. These modifications areconsistent with a reduction in solar modulation, providing a viable explanation for the exceptional GCRintensities in interplanetary space.